2013
DOI: 10.1021/ol401666e
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II)-Catalyzed Asymmetric Intramolecular Aminohydroxylation of Indoles

Abstract: An enantioselective intramolecular indole aminohydroxylation reaction is catalyzed by iron(II)-chiral bisoxazoline (BOX) complexes (ee up to 99%, dr > 20:1). This discovery enables expedient asymmetric synthesis of a series of biologically active 3-amino oxindoles and 3-amino indolanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 66 publications
(18 reference statements)
0
17
1
Order By: Relevance
“…Under the same conditions, but in the presence of a carboxylic acid, indole systems 93 undergo 1,2‐aminooxygenation to provide products 94 (Scheme 30B). This method is complementary to other recently reported indole 1,2‐aminooxygenation processes [69–71] . For indole systems, it was proposed that excitation of the Ru(II) photocatalyst leads to reductive cleavage of Bl−OAc to provide BI‐radical 95 .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Under the same conditions, but in the presence of a carboxylic acid, indole systems 93 undergo 1,2‐aminooxygenation to provide products 94 (Scheme 30B). This method is complementary to other recently reported indole 1,2‐aminooxygenation processes [69–71] . For indole systems, it was proposed that excitation of the Ru(II) photocatalyst leads to reductive cleavage of Bl−OAc to provide BI‐radical 95 .…”
Section: Discussionmentioning
confidence: 59%
“…1,2-aminooxygenation processes. [69][70][71] For indole systems, it was proposed that excitation of the Ru(II) photocatalyst leads to reductive cleavage of BlÀ OAc to provide BI-radical 95. This abstracts the hydrogen atom from the NÀ H unit to provide an electrophilic nitrogen centered radical that undergoes 5-exo cyclization onto the indole unit.…”
Section: R E C O R D R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
“…903 This method led to an enantioselective synthesis of spiro[indoline-3,4 0 -oxazolidine] derivatives which are suitable precursors for biologically relevant 3-aminooxindoles and 3-aminoindolanes.…”
Section: Càheteroatom Bond Forming Additions To Càc Double and Triplementioning
confidence: 99%
“…Al iterature search showed that there are three different ways to realize intramolecular oxyamination of ad ouble bond:a )byc yclization of unsaturated nitrogen-containing compounds in the presence of an external oxygen source (which leads to the formation of an itrogen-containing heterocycle); [8] b) by cyclization of unsaturated oxygen-containing compounds in the presence of an external nitrogen source (resulting in the formation of an oxygen-containing heterocycle); [9] c) by cyclization of unsaturated compounds that contain aN ÀOb ond, which is cleaved during the process. [10] It is worth noting that there are many more reports on nitrogen-based (a) [8] than oxygen-based (b) [9] intramolecular oxyaminations.F urthermore,t he examples of intramolecular oxyaminations from compounds containing an N À O bond (c) [10] are quite rare and they always involve the formation of an oxygen-substituted nitrogen-containing heterocycle.T he formation of as aturated oxygen-containing heterocycle of type E from an O,w-unsaturated alkoxyamine is,t ot he best of our knowledge,t he first example of such atransformation.…”
mentioning
confidence: 99%